Muhammad and Syrian Monasticism - Blázquez Martínez, José María (Gerión. Revista de Historia Antigua, 2013)
This paper compares fundamental aspects of religiousness in the Qur’an with that of Syrian Monasticism. Muhammad is a Christian heretic according to Saint John of Damascus, who lived many years in the Umayyad court, where he held important posts. The great protestant investigators of the 20th century –Harnack, Schlatter, Wellhausen– maintain he was an Ebionite, in other words, a heterodox Jewish Christian, who lived in Palestine and Syria. A thesis accepted by the great catholic t heologian H. Küng, a supporter of dialogue with Islam. Muhammad lived at the beginning a mountain life, very similar to that of Christian monks. A strong influence of Palestinian and Syrian Monasticism in Muhammad’s religiousness can’t be put in question, as D. J. Sahas, an excellent connoisseur of Saint John of Damascus and Muhammad, points out. The religiousness of Muhammad, of Syrian Monasticism and of Jesus have strong social character, like that of the great prophets of Israel. This paper confirms the sentence of Seyyed Husseyn Nasr, that primitive Muslims were monks who did not keep up with celibacy.
Keywords: Palestinian Monasticism influence; Qur’an; Hell; Last Judgement; Demonology; Paradise; Angeology; Fasting; Alms; Food prohibition; Peregrinations; Revelations and Inspirations; Eucharist; Christology; Ebionite; Jewish Christian; Mountain; Monks.